Chemical and mechanical properties of pellets made from agricultural and woody biomass blends - Harun, N.Y. (American Society of Agricultural and Biological Engineers, 2015)
Traditionally, the pellet industry depends heavily on forestry biomass. Large amounts of agricultural residues are generated every year and have the potential to be used as alternative feedstocks for pellet production. The aim of this study was to analyze the chemical (mineral content, proximate and ultimate analyses, thermogravimetric analysis), physical (porosity, particle size), and mechanical (durability and strength) properties of agricultural (reed canary grass, timothy, and switchgrass) and woody (spruce and pine) biomass pellets and their blends. Agricultural and woody biomass were blended in ratios of 25:75, 50:50, and 75:25. The biomass pellets were formed using a closed-end plunger-die assembly attached to an Instron machine. An increase in the volatile and char contents of the blended biomass was observed using thermogravimetric analysis. This was further confirmed by an increase in the carbon and hydrogen contents of the blended biomass. A significant decrease in chloride was observed after blending. The strength of the blended biomass pellets was inversely proportional to the particle size. The pellet durability index (PDI) of pure agricultural biomass pellets was less than 90, which is well below the Pellet Fuels Institute (PFI) standard requirement. This study revealed that it was possible to achieve PDI greater than 95 using a blend ratio of 50:50. Similarly, the pellet strength of the blended biomass was higher compared to individual agricultural biomass. In conclusion, this study confirms that agricultural biomass can be mixed with forestry biomass to develop an alternative feedstock for the pellet fuel industry. Â© 2015 American Society of Agricultural and Biological Engineers.